Reconstructing Ijtihad Fiqh in Responding to the Challenges of Artificial Intelligence: An Ethical and Sharia Legal Analysis in the Digital Era - Nandika Rizki Fitrian Ramadhani; Wahyu Kholis Prihantoro; Hanif Atha Fallah; Muhammad Syaifulloh; Laily Mazilatul Magfiroh; Amalia Rahmah; Dea Syafa Fatimah (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2026)
This study aims to analyze the urgency and forms of reconstructing fiqh Ijtihad in responding to the challenges of AI while remaining grounded in the principles of Sharia. This study employs a literature review method with a descriptive qualitative approach, examining classical and contemporary fiqh literature, the concept of maq??id al-syar?‘ah, fatwas from religious institutions, and academic studies on the ethical and legal implications of AI. The research findings indicate that the development of AI raises a number of critical issues, such as data privacy protection, accountability for algorithmic decisions, the potential for bias in intelligent systems, the spread of misinformation, and the use of AI in religious services and practices. The complexity of these issues cannot be adequately addressed through the traditional, linear approach of qiy?s; therefore, a more progressive and contextual approach to Ijtihad is required, such as maq??id-based Ijtihad, collective Ijtihad involving scholars and technology experts, and methodological integration between u??l al-fiqh and modern technological analysis. This study concludes that the reconstruction of fiqh Ijtihad is a strategic step and a necessity to ensure that the use of AI remains within the framework of Islamic values and enables fiqh to function as an adaptive normative guide to the dynamics and challenges of the digital age.